ORPLocator: Identifying read points of configuration options via static analysis - DONG, Zhen (Institutional Knowledge at Singapore Management University, 2016)
Configuration options are widely used for customizing the behavior and initial settings of software applications, server processes, and operating systems. Their distinctive property is that each option is processed, defined, and described in different parts of a software project - namely in code, in configuration file, and in documentation. This creates a challenge for maintaining project consistency as it evolves. It also promotes inconsistencies leading to misconfiguration issues in production scenarios. We propose an approach for detection of inconsistencies between source code and documentation based on static analysis. Our approach automatically identifies source code locations where options are read, and for each such location retrieves the name of the option. Inconsistencies are then detected by comparing the results against the option names listed in documentation. We evaluated our approach on multiple components of Apache Hadoop, a complex framework with more than 800 options. Our tool ORPLocator was able to successfully locate at least one read point for 93% to 96% of documented options within four Hadoop components. A comparison with a previous state-of-the-art technique shows that our tool produces more accurate results. Moreover, our evaluation has uncovered 4 previously unknown, real-world inconsistencies between documented options and source code